2006
DOI: 10.1111/j.1468-0122.2006.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Every Child Know They Matter? Pupils' Views of One Alternative to Exclusion

Abstract: Schools are now urged to make every child matter. In this paper we present the case of the Coalfields Alternatives to Exclusion (CATE) strategy in which pupils at risk of permanent exclusion are offered the opportunity to start afresh in a new school. Without the stigma of exclusion, pupils are able to develop new relationships with peers and teachers and enhance self-esteem. We argue that this system of managed moves, despite some difficulties and challenges, offers an insight into the ways in which feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Integral to this was the formation of relationships with staff that were characterised by trust and respect. We have argued that this relational change is a necessary first step in the practices of inclusion (Harris et al 2006). We now explore some of the events and processes that engendered these feelings, allowing these qualitatively different relationships to develop and we look at what this reveals about creating more inclusive schools.…”
Section: Moving Towards Inclusion: What Work?mentioning
confidence: 99%
See 2 more Smart Citations
“…Integral to this was the formation of relationships with staff that were characterised by trust and respect. We have argued that this relational change is a necessary first step in the practices of inclusion (Harris et al 2006). We now explore some of the events and processes that engendered these feelings, allowing these qualitatively different relationships to develop and we look at what this reveals about creating more inclusive schools.…”
Section: Moving Towards Inclusion: What Work?mentioning
confidence: 99%
“…There was support for CATE across all stakeholder groups, although a number of issues and concerns were also noted (see Harris et al, 2006). This paper focuses primarily on outcomes, both 'hard' and 'soft', that relate directly to the pupils themselves.…”
Section: What Difference Does Cate Make For Pupils Their Families Anmentioning
confidence: 99%
See 1 more Smart Citation
“…To compound these difficulties, students with EBD have their voices heard the least, are empowered the least, and are the least liked group of students (Baker, 2005;Cooper, 2006;Lewis & Burman, 2008). With all of these obstacles to success, students with EBD have indicated that the relationship that they have with teachers is one of the most important factors in their success (Cefai & Cooper, 2010;Garner, 1993;Harris, Vincent, Thomson, & Toalster, 2006;Jahnukainen 2001;Pear, 1997;Sellman, 2009;).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cuts to local authority provision, the development of school-run collaborative processes for young people excluded from school, the growth of 'managed moves' programmes (Abdelnoor, 2007;Harris, Vincent, Thomson, & Toalster, 2006;Vincent, Harris, Thomson, & Toalster, 2007) and a recent trial to test out schools' capacity to commission all of their own alternative education provision (Institute of Education (University of London) and the National Foundation for Educational Research ( NFER), 2013) have all contributed to a significant increase in complementary AE. This expanded AE is either run by schools themselves or with a small group of 'preferred providers' (Institute of Education (University of London) and the National Foundation for Educational Research ( NFER), 2014).…”
Section: Alternative and Complementary Alternative Educationmentioning
confidence: 99%